Comparative Evaluation between Local and Spinal Anaesthesia for Inguinal Mesh Hernioplasty in Elderly Patients with Limited Cardiac Reserve - Paudel, Bandana; Paudel, Sumitra; Chapagain, Saugat; Das, Chitta Ranjan (Journal of Nobel Medical College, 2016)
Background The choice of anaesthesia technique, based on its advantages and disadvantages in elderly patients with limited cardiac reserve will be influenced by the patient’scomorbid diseases. The aim of the study was to compare the effects of spinal anaesthesia and local anaesthesia in elderly patients with limited cardiac reserve for inguinal mesh hernioplasty. Material and Methods In the present study 60 male patients between the ages of 65 to 92 with limited cardiac reserve, reported for mesh hernioplasty were equally divided in two groups. One group received spinal anaesthesia (SA) and the other group received local anaesthesia with nerve block (LA). Effectiveness and complications of both the group were evaluated. Results All patients had comorbid cardiac diseases with limited cardiac reserve along with hernia. Perioperative and postoperative complications were significantly more in SA group. All the surgeons and patients were satisfied with the operating conditions. Conclusion Nerve block anaesthesia with skin infiltration for inguinal mesh hernioplasty in elderly patients with limited cardiac reserve is recommended, as it is safe, patient friendly with less postoperative complications. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 49-56